2021
DOI: 10.1371/journal.pone.0257186
|View full text |Cite
|
Sign up to set email alerts
|

Maternal PCOS status and metformin in pregnancy: Steroid hormones in 5–10 years old children from the PregMet randomized controlled study

Abstract: Objective Polycystic ovary syndrome (PCOS) is a common endocrine disorder, with potential effects on offspring both genetically and through altered intrauterine environment. Metformin, which ameliorate hormonal disturbances in non-pregnant women with PCOS is increasingly used in pregnancy. It passes the placenta, and the evidence on potential consequences for offspring endocrine development is scarce. We explore the potential effects of maternal PCOS status and intrauterine metformin exposure on offspring ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…A total of 3,149 records were included in the initial search, and 2,837 remained after duplicates were removed. After excluding articles that did not meet the inclusion criteria, 48 studies were full-text screened, and finally 18 articles were determined to be eligible and included in this analysis (Figure 1) (1,(9)(10)(11)(12)(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3,149 records were included in the initial search, and 2,837 remained after duplicates were removed. After excluding articles that did not meet the inclusion criteria, 48 studies were full-text screened, and finally 18 articles were determined to be eligible and included in this analysis (Figure 1) (1,(9)(10)(11)(12)(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, whether metformin is associated with metabolic profile and sex hormone levels also remain a subject of debate. Recent published studies showed controversial results of fasting glucose and SHGB hormone levels (9,(14)(15)(16). The small sample size of the studies might contribute to the various and inconsistent results, thus it is necessary to develop a meta-analysis to assess the efficacy of metformin.…”
Section: Introductionmentioning
confidence: 99%
“…While nonparametric hormone references represent clinical cutoff values and primarily provide a qualitative indication as to whether the patient is within or outside the reference interval, LMS models enable quantitative benchmarking and longitudinal tracking of patients’ biomarker levels in terms of z-scores. This feature was recently leveraged to quantify endocrine abnormalities in a pediatric cohort that were exposed to metformin in utero due to treatment of maternal polycystic ovary syndrome ( 22 ). Applying reference curves to monitor individual patients over time may also be useful for evaluating pediatric endocrinopathies, differences of sex development, and general follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we hypothesized that pediatric overweight may be associated with an altered endocrine profile that, in particular, may be characterized by increased levels of estrogens due to increased adipose tissue aromatase activity. The current reference curves have not been published previously but were recently used to benchmark biomarker z-scores in an unrelated cohort of children exposed to metformin in utero due to maternal polycystic ovary syndrome ( 22 ).…”
mentioning
confidence: 99%
“…70,71 Interestingly, in the same study subanalysis when disaggregated by foetal sex, Metformin showed a modest decrease in maternal androgen levels during pregnancy for women with female foetuses, although no effect was observed in the androgen levels of the girls subsequently at age 5-10 years. 72 A recent meta-analysis of children born to women with GDM or PCOS found that Metformin intake in pregnancy was associated with higher long-term weight in children. 73 Given the positive effects of Metformin in systemic level, 74 it seems rational to use Metformin as a pre-pregnancy treatment for weight management although the role of Metformin on improving pregnancy rate or live birth rate is still debatable 75,76 and the benefit seems to be linked to ovulation induction rather than IVF/ICSI.…”
Section: Medicationsmentioning
confidence: 99%